The Effectiveness of E-Learning Platform in Higher Institutions: A Review on Language, Psychology, and Culture - Welsi Haslina; Lilimiwirdi Lilimiwirdi (JURNAL ARBITRER, 2022)
The effectiveness of e-learning has some uniqueness and challenges in terms of obstacles faced, and its learning model. This research employs the observation method by observing both spoken and written data, survey, and interview. Data was obtained from 80 higher institutions students and 50 lecturers of four state-owned institutions, and four private institutions.The results show that the effective learning conducted through e-learning has met the expected standard. Through the learning process, the students were provided by motivational training, and educated with character building based on their religious belief. Moreover, the lecturers carried out their teaching process through WhatsApps Group, zoom meeting and/ or google meet applications, and provided the students with instructions and guidance. The instructions and guidances were particularly concerned on how to conduct the online classes with the camera on, comprehending the Semester’s Lesson Plan (SLP) for the whole semester, providing feedback on the materials, examples, video assignments, and weekly tasks given. Besides that the instructions and guidances were also specified for the students to seize the opportunities to present their tasks virtually. Likewise, the supports from the institutions are also needed concerning the committee for quality assurance in the implementation of E-learning, draft, attendance list, journal, contract of the course, motivational to the lectures in implementing E-learning, and video conference room (Vicon) as well.